2012
DOI: 10.1210/jc.2012-1213
|View full text |Cite
|
Sign up to set email alerts
|

The Level of Serum Anti-Müllerian Hormone Correlates with Vitamin D Status in Men and Women But Not in Boys

Abstract: Vitamin D may be a positive regulator of AMH production in adults, and vitamin D deficiency may confound clinical decisions based on AMH. Vitamin D deficiency should be considered when serum AMH levels are obtained for diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
106
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(125 citation statements)
references
References 37 publications
4
106
1
3
Order By: Relevance
“…Previous studies were investigated the relationship between vitamin D and ovarian reserve status. Although our results do not agree with these studies, human studies have reported positive correlations between serum 25(OH) D and AMH levels (11,16,17). Merhi et al found a weak negative association between vitamin D and AMH levels in women under 35 years of age and a weak positive relationship above 40 years of age (10).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Previous studies were investigated the relationship between vitamin D and ovarian reserve status. Although our results do not agree with these studies, human studies have reported positive correlations between serum 25(OH) D and AMH levels (11,16,17). Merhi et al found a weak negative association between vitamin D and AMH levels in women under 35 years of age and a weak positive relationship above 40 years of age (10).…”
Section: Discussioncontrasting
confidence: 99%
“…However, serum AMH levels were mostly very low and even sometimes non-measurable as expected in such women. Dennis et al conducted a study, which was one of first studies reporting that vitamin D might exert a positive impact on AMH production (16). Nevertheless, the study population was small and did not consider the ovarian status.…”
Section: Discussionmentioning
confidence: 99%
“…Although AMH is one of the best markers of ovarian reserve, it has been shown to be altered by environmental factors such as obesity and vitamin deficiencies [6,[8][9][10][11]. For instance, we have recently shown that circulating vitamin D level may play a role in predicting serum AMH especially in late reproductive-aged women who are more likely to have DOR than early reproductive-aged women [7].…”
Section: Discussionmentioning
confidence: 99%
“…Serum AMH levels estimate ovarian reserve and the proximity of menopause [3]. Although we and others [4][5][6][7][8][9][10][11][12] have recently shown that Capsule AMH of 0.2 ng/mL appears to be a clinically meaningful cutoff for predicting a relatively "good" clinical pregnancy rate in women with severely diminished ovarian reserve at our practice. serum AMH is affected by several factors including obesity, serum leptin and serum vitamin D; AMH remains one of the most reliable markers of ovarian reserve and is commonly used in assisted reproductive technology (ART) as a predictor of ovarian response in ovarian stimulation protocols in women with normal or diminished ovarian reserve (DOR) [13][14][15].…”
Section: Introductionmentioning
confidence: 95%
“…It has been also reported that AMH level increases with increasing serum 25-hydroxyvitamin D (25OH-D) level in women ≥40 years of age 5) 6) . In addition to serum vitamin D levels, premenopausal women show seasonal variations in serum AMH levels, showing an 18% decrease in serum AMH levels in winter compared to summer 5) . Vitamin D has also been shown to affect AMH gene expression in vitro 7) .…”
mentioning
confidence: 99%